EFEKTIVITAS MODEL PEMBELAJARAN STUDENTS FACILITATOR AND EXPLAINING (SFE) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMK NEGERI 1 BATANG ANGKOLA - Rina Rangkuti (JURNAL MathEdu (Mathematic Education Journal), 2019)
ABSTRACT The aimof this studyis to describe the effectiveness of using SFE learning model on students’ mathematical communication ability on the topic two- variables linier equation system at the tenth grade students of SMK Negeri 1 Batang Angkola. This research was conducted by applying experimental (one group pre test post test design) with 32 students as the sample and they were taken by using simple random sampling technique from 135 students.Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using SFE learning model was 2.43 (good category) and (b) the average of students’ mathematical communication ability on the topic two- variables linier equation system before using SFE learning model was 38.80 (poor category) and after using SFE learning model was 81.87 ( very good category). Furthermore, by using pair sample ttest and N-Gain, the result showed the significant value was less than 0.05 (0.000<0.05 and g= 0.70 (middle category). It means, SFE learning model was effective used on students’ mathematical communication ability on the topic two- variables linier equation system at the tenth grade students of SMK Negeri 1 Batang Angkola. Keywords: effectiveness, SFE learning model, communication ability